Penegakan Hukum Terhadap Tindak Pidana Penipuan Calon Jemaah Umroh - Sigit Prihanto (UNISSULA Semarang, 2020)
The fraud of prospective jemaah umrah in Indonesia has recently become one of the many cases that concern the public. This is because the number of people who become victims with the amount of losses reaching billions rupiah. The enforcement of the law during the case of jemaah umroh in Indonesia has prioritized general law in its investigation process. Police in particular, as the front guard in their law enforcement process through investigation, tend to use the Criminal Law as a basis in processing suspects. One of the principles of criminal law is a special law that excludes general law, known as lex specialis derogat legi generali. The thoroughness in law enforcement process is what should be done by law enforcers in handling cases of fraud against prospective jemaah umroh that happen in Indonesia.Keywords: Law enforcement, Fraud, Jemaah Umroh/ Umroh Goups